2013
DOI: 10.1007/s12291-012-0292-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Insulin Resistance and Metabolic Syndrome in Drug Naive Patients of Bipolar Disorder

Abstract: The levels of fasting glucose, fasting insulin, insulin resistance (IR) and the prevalence of metabolic syndrome (MS) in a sample population of bipolar disorder (BPD) patients who were newly diagnosed and psychotropically naïve were assessed and compared with an age, sex and racially matched control population. 55 BPD-I patients (15-65 years) who were non-diabetic, nonpregnant, and drug naïve for a period of at least 6 months were included in the study. Diagnosis was made using the structured clinical intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 28 publications
3
40
1
Order By: Relevance
“…In patients with FEP, our cumulative analyses on glucose metabolism outcomes are in line with previous meta‐analyses, which showed significant increases in fasting insulin levels and impaired oral glucose tolerance in this patient population (Greenhalgh et al, ; Perry et al, ; Pillinger et al, ). Our meta‐analysis also confirms previous reports of an impaired oral glucose tolerance in first episode, treatment‐naïve patients with mood disorders (Garcia‐Rizo et al, ; Guha et al, ). Previous studies mostly focused on a specific diagnosis of SMIs, particularly FEP, while only one study compared the differences on glucose metabolism outcomes between various SMIs (Garcia‐Rizo et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In patients with FEP, our cumulative analyses on glucose metabolism outcomes are in line with previous meta‐analyses, which showed significant increases in fasting insulin levels and impaired oral glucose tolerance in this patient population (Greenhalgh et al, ; Perry et al, ; Pillinger et al, ). Our meta‐analysis also confirms previous reports of an impaired oral glucose tolerance in first episode, treatment‐naïve patients with mood disorders (Garcia‐Rizo et al, ; Guha et al, ). Previous studies mostly focused on a specific diagnosis of SMIs, particularly FEP, while only one study compared the differences on glucose metabolism outcomes between various SMIs (Garcia‐Rizo et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Epidemiological studies have indicated higher DM2 incidence, as well as increased insulin resistance in patients with bipolar disorder and depression (Calkin et al, 2013;Charles, Lambert, & Kerner, 2016;Fagiolini, Frank, Scott, Turkin, & Kupfer, 2005;McIntyre et al, 2005;Roy & Lloyd, 2012). Furthermore, findings in treatment-naïve first episode patients with bipolar disorder (Garcia-Rizo et al, 2016; Guha et al, 2014) and depression (Chang et al, 2013;Garcia-Rizo et al, 2013) indicated impaired glucose tolerance, insulin resistance and increased rates of DM2, similar as FEP patients. Impaired glucose metabolism may thus be a non-specific finding common to SMIs near illness onset.…”
Section: Introductionmentioning
confidence: 98%
“…A further explanation for the highly elevated HOMA-IR values seen in this study could be the already elevated insulin resistance seen in medication-naive bipolar disorder. Guha and colleagues compared insulin resistance and metabolic syndrome components in a cohort of newly diagnosed, medication-naive bipolar I subjects to healthy controls [46] . The authors showed that insulin resistance was significantly higher in the bipolar disorder subjects compared with controls (HOMA-IR 3.16 vs 1.19, respectively) and that HOMA-IR was not predicted by age, sex, waist circumference or mood status.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time the type of current mood episode in bipolar disorder was not predictive of the presence of metabolic syndrome or insulin resistance [150]. …”
Section: Similarities and Differences Between Essential Hypertensimentioning
confidence: 99%